3(-4x+1)=x+5=-3

Simple and best practice solution for 3(-4x+1)=x+5=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-4x+1)=x+5=-3 equation:



3(-4x+1)=x+5=-3
We move all terms to the left:
3(-4x+1)-(x+5)=0
We multiply parentheses
-12x-(x+5)+3=0
We get rid of parentheses
-12x-x-5+3=0
We add all the numbers together, and all the variables
-13x-2=0
We move all terms containing x to the left, all other terms to the right
-13x=2
x=2/-13
x=-2/13

See similar equations:

| w/8+5=7 | | 6*x*x-12*x-15=0 | | -n-8(1+7n)=-8 | | 10w+8=98 | | 8x-56=4 | | 6*x*x-12*x+15=0 | | 6x+1=1+5x-(-x) | | x^2+7=x+ | | 11=-w | | 19=3a- | | -5/6x+25=-15 | | -10r–10=10 | | 2t+8+1/5t-t=11 | | 8(y-3y=6(2y-6 | | -6.5+x=14.12 | | -4x+8+5x=-13+17 | | 1x-9=-12 | | 3r^2-20r-7=0 | | 1–8z=9 | | 10r–10=10 | | f=4-8 | | |5x-5|/4=5 | | 8/5x+4/3=1/15 | | -7+8n=9 | | 9x2-5=-23 | | 42/y=2 | | 24+0.44=19+1.69x | | x(6x-13)=5 | | 2z-3=-7 | | 12m+9=8m+13 | | 10n-14=7n-16+3n+2 | | 1x(6x-13)=5 |

Equations solver categories